Juicylicious Company / Akmal Nashreq Abd Malik... [et al.] - Abd Lasim, Mohd Hussin; Dariman, Mohd Hambali; Mohammad, Mohd Tawfiq; Jaludin, Nur Hafizah; Usin, Suhana; Abd Malik, Akmal Nashreq (2013)
We take our business based on impression about high quality bar where people will stay for relaxing. We use the juicy symbol as our representatives of our company. Our company is "Juicylicious Bar Enterprise". Our business is based on partnership which includes 6 persons of our members who have certain qualification and experience work in business management at the several company in our country. As related, our company name Juicylicious Bar is derived from the word of combination of Juice and Delicious. It's mean that juice is delicious and its good for the bar. For nowadays the word of Bar is officially use to call a place where people will hang out together. For example, the persons who interpret the culture, manga collector, games etc. We have chosen to open the business as a fact that nowadays there are many Bar that Hon Halal in various country. So we have came out with this business where our Bar is Halal and allowed to enter for everyone. Bar also been known by various people in the country or the other country. This is also our main purposes of existing the Juicylicious Bar which is also a kind of good services that are prepared to our people that are fans and interest for relaxing. Our company provided a lot of variety foods and drink and variety activity, such as, Dart, Pool and game for our customer and much more. We chosen the good and quality services based on what people like or deserve.